DETECTION AND CONTROL OF SCRAP IN THE INTERNAL CLIENT THROUGH AN SAP SYSTEM: case study - da Silva Junior, Renato; Rodolpho, Daniela (Revista Interface Tecnológica, 2023)
The SAP system, encompasses all areas in the production process, helping companies in the most diverse stages of the manufacturing process and decision making, through development, the company in the study uses the aggregation of the areas allowed by the software and performs its control and detection of scraps through SAP as too quality tools, the study in question will analyze how the company performs the control, from the detection in the factory to the actions so that the defects do not happen again, the analysis of the daily weekly indicators and psychological and from where the information for the thought of cause is taken. They also consider whether the actions taken are effective or imperfect, the work methodology of the group that refers to the company X and its dealings when a defect is detected, how the areas are involved, from the creation of a work group to the change in work procedures and internal factory rules.
Keywords: SAP System; Quality Tools; Indicators; Scraps